Sandplay therapy could be a method to decrease disease activity and psychological stress in children with systemic lupus erythematosus. (February 2022) - Li, Jinjiao; Shi, Yanjun; Zhou, Wei
Objective: Although the prevalence rate of childhood-onset systemic lupus erythematosus (cSLE) is far lower than that of adults, cSLE has a high rate of organ involvement, rapid development and poor prognosis, which is more serious than that in adults. And studies have shown that a wide range of physiological, functional, nerve, and organ damage will have a great impact on the mental health of children. At present, there is no relevant psychological intervention research for cSLE in China. This paper aimed to explore the effect of Sandplay therapy on mental health and disease activity of children with cSLE. Methods: Forty childrens with cSLE were randomly divided into control group (CG) and intervention group (IG); the CG were treated with glucocorticoid, immunosuppressant and other drugs, while the IG were treated with Sandplay therapy in addition to drug therapy, at the time of 0, 2, and 4 weeks after initial diagnosis, respectively. The questionnaire evaluation and related clinical indicators of the two groups were compared and analyzed (before psychotherapy intervention) at 0, 2, 4, and 12 weeks after initial diagnosis. Results: There was no significant difference between the two groups in the evaluation of questionnaire and related clinical indicators at the time 0, 2 weeks after initial diagnosis respectively. At 12 weeks after the intervention, the score of Short version of the Children's Depression Inventory (CDI-S) in the IG was significantly lower than that in the CG, the score of The Screen for Child Anxiety Related Emotional Disorders (SCARED) scale in the IG was significantly lower than that in the CG, and the Pediatric Quality of Life Inventory (PedsQL 4.0) showed that the scores of social function, school performance, and emotional health of the IG were higher than those of the CG ( p < 0.05), and the clinical indexes of the IG were better than those of the CG ( p < 0.05). Conclusion: Sandplay therapy may help to slow down the occurrence and development of anxiety and depression and reduce disease activity in patients with cSLE.